Asuhan Keperawatan Gangguan Pola Tidur Melalui Terapi Audio Murottal Dengan Sleep Quality Indek Pada Lansia - Maritta Sari; Aulia Ramadhani (Gayaku Publisher, 2022)
The purpose of this study was to provide nursing care for sleep pattern disorders through murottal therapy in the elderly with hypertension. This research method uses qualitative research in the form of case studies to explore the problem of nursing care for sleep disorders through murottal therapy in the elderly with hypertension. The approach used is a nursing care approach which includes assessment of nursing diagnoses, planning, implementation and evaluation. The results showed that there was an increase in sleep quality and quantity after murottal therapy in the elderly with sleep pattern disorders with hypertension for 7 consecutive days.